Traumatic Lateral Spondyloptosis of the Lumbar Spine: A Case Series and Comprehensive Literature Review - L. Erin Miller; Emal Lesha; Jordan T. Roach; Garrett T. Venable; William Mangham; Mallory Dacus; Deke Blum; Michael S. Muhlbauer; Raul J. Cardenas (Journal of Spine Practice)
Introduction: Lateral spondyloptosis of the lumbar spine is a rare and devastating form of traumatic spinal injury. Given the paucity of lumbar lateral spondyloptosis case reports in the literature, the authors seek to inform readers of the clinical, radiological, and operative considerations for three patients with this uncommon clinical presentation, as well as provide a comprehensive review of the literature on this topic.